Principios Procesales del Amparo Constitucional - Peñaranda Quintero, Héctor Ramón (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The constitutional procedural shelter intends to assure the enjoyment of the constitutional rights and guarantees that are established in the Constitution, international laws and treaties, condemn the aggressors action from all citizen, public or deprived organizations; tending solely to the establishment of the violation or threat of violation of the constitutional right or guarantee. Looking forward to recovering total enjoyment and exercise of such rights.
Keywords: Shelter; Constitution; Resource; Fundamental rights